2015
DOI: 10.1039/c5ra05687j
|View full text |Cite
|
Sign up to set email alerts
|

Cation assisted complexation of octacarbazolylphenyl substituted Zn(ii)-tetraphenylporphyrin with [2,2,2]cryptand

Abstract: Supramolecular complex formed from a carbazolylphenyl-porphyrin first generation dendrimer and [2,2,2]cryptand was prepared and investigated the influence of alkali metal cations on its formation and properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…In the reports [ 13 , 14 , 15 , 16 , 17 ], devoted to the formation of supramolecular porphyrin complexes with several binding points, the contributions of axial coordination energy (Δ G axial coord. ) and H-bonds (Δ G HB ) to the total energy of the complex formation were estimated.…”
Section: Results and Its Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the reports [ 13 , 14 , 15 , 16 , 17 ], devoted to the formation of supramolecular porphyrin complexes with several binding points, the contributions of axial coordination energy (Δ G axial coord. ) and H-bonds (Δ G HB ) to the total energy of the complex formation were estimated.…”
Section: Results and Its Discussionmentioning
confidence: 99%
“…[ 6 , 7 , 8 , 9 , 10 ], depending on the nature of the central metal cation. The most metalloporphyrin receptors described in the literature are hydrophobic Zn(II)-porphyrins [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], which form supramolecular complexes with substrates in the organic media (dichloromethane, chloroform, benzene, or toluene). Hydrophilic Co(III)-porphyrins are characterized by a high binding ability towards various nitrogen-containing biomolecules in aqueous, biological media [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cryptand nitrogen atoms and the porphyrinate metal cation act in this case as the binding centers. The authors of [ 110 ] studied the formation of a complex between zinc porphyrinate 82 and cryptand-2,2,2 (Cr1) as a model system. It is shown that the electronic absorption spectra of the reaction system have one family of spectral curves with its own set of isobesticpoints ( Figure 24 a).…”
Section: Molecular Receptors Based On Porphyrins Modified At the Macrocycle Periphery With Bulky Substituentsmentioning
confidence: 99%
“…The structure of the receptor-substrate complex was verified by the 2D ROESY NMR method. It should be said that a lot of works describe the binding ability of macrocyclic receptors with well-defined geometries [105][106][107][108][109][110][111]. An analysis of the presented data indicates that their complexing ability is strongly dependent on the conformational mobility of the lateral substituents (molecular fragments) and the possibility of formation of intramolecular cavities and channels of various shapes within them.…”
Section: Molecular Receptors Based On Porphyrins Modified At the Macrocycle Periphery With Bulky Substituentsmentioning
confidence: 99%
See 1 more Smart Citation